Benefits of exposure. Issue 4 (10th November 2014) - Fox, Robert
Abstract : Purpose: – This column aims to look at various aspects of search engine optimization (SEO) and the potential risks and rewards from exposing library-related content using techniques such as microdata and descriptive frameworks such as that outlined on schema.org. Design/methodology/approach: – Regular column. Findings: – This column explores concepts related to SEO and is speculative in nature. Originality/value: – Academic libraries can greatly benefit from exploring the potential benefits of using SEO and microdata/microformats. The landscape for SEO has changed dramatically over the past decade, and the benefit to libraries who have in once sense seen themselves as competitors with the major search engines is significant.